2017
DOI: 10.1515/ohs-2017-0040
|View full text |Cite
|
Sign up to set email alerts
|

Bathymetric distribution of macroinvertebrates in the Northeastern Levantine Sea and the Northeastern Aegean Sea based on bottom-trawl surveys

Abstract: The objective of this study was to compare the distribution patterns of macroinvertebrate species between the Northeastern Levantine Sea and the Northeastern Aegean Sea. A total of 157 hauls were carried out by commercial trawlers at depths ranging from 30 to 410 m in both areas. The result of SIMPER analysis shows clear differences between the two surveyed areas except for the 300-410 m depth range. Ninety five species were found in the Northeastern Aegean Sea and 100 species in the Northeastern Levantine Sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The Atlantic brisingid Hymenodiscus coronata is a common encounter on the Mediterranean bathyal muds, e.g., [1,2,18,29], that has only been observed as scattered individuals or small groups of few specimens until now, e.g., [3,24,28,31]. This work reports, for the first time, in the Mediterranean Sea, the observation in situ of aggregations of this species in the Strait of Sicily, with novel information on its distribution, morphology, ecology, and vulnerability.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The Atlantic brisingid Hymenodiscus coronata is a common encounter on the Mediterranean bathyal muds, e.g., [1,2,18,29], that has only been observed as scattered individuals or small groups of few specimens until now, e.g., [3,24,28,31]. This work reports, for the first time, in the Mediterranean Sea, the observation in situ of aggregations of this species in the Strait of Sicily, with novel information on its distribution, morphology, ecology, and vulnerability.…”
Section: Discussionmentioning
confidence: 90%
“…Most of the information on the distribution of this species comes from trawling surveys. It has been documented from the North-eastern Atlantic Ocean, from Norway to the Canary Islands [22,23], and throughout the Mediterranean Sea, both in the western and the eastern basins [2,[24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…In the eastern Mediterranean Sea, H. barbata was recorded from Greece (Lucas,1853;Raulin, 1870;Kevrekidis & Galil, 2003;Kampouris et al, 2018), Cyprus (Hadjichristophorou, 1997;Kocataş et al, 2001), Syria (Ammar & Hmaesha, 2023), Lebanon (Shiber, 1981), Israel (Holthuis & Gottlieb, 1958), Egypt (Ramadan & Dovidar, 1972), and Türkiye (Karhan, 2015;Deval et al, 2017;Gönülal & Dalyan, 2017;Patania & Mutlu, 2021) (Figure 1; Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Besides these studies, Özcan et al (2009a) and Gönülal et al (2014) reported 1 and 3 species, respectively, from the region. Subsequently, an anomuran species, Galathea bolivari Zariquiey Álvarez, 1950, was reported from the deep waters of the Turkish Aegean by Gönülal and Dalyan (2017), although this species has been described in various studies as a species distributed in shallow waters (i.e. Geldiay and Kocataş, 1970;Noël, 1992;Falciai and Minervini, 1996;Koçak and Katağan, 2008).…”
Section: Introductionmentioning
confidence: 99%